Pengaruh Kontrol Diri Terhadap Criminal Thinking Tahanan dan Narapidana di Rutan Kelas I Surakarta - Yuliana Novitasari; Maki Zaenudin Subarkah (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
Criminal thinking can be interpreted as a condition of a person's thinking to commit a desired criminal act by going against the existing rules through justifications for actions that are considered true and common. The criminal thinking process can be controlled by being given the right treatment in order to restore the thinking process according to the applicable norms and rules. This study has a purpose to determine the effect of self-control on criminal thinking of prisoners at Correctional Institution Class I Surakarta. The research method used is quantitative method by distributing questionnaires. Sampling using stratified random sampling as many as 86 respondents of prisoners at Correctional Institution Class I Surakarta. The questionnaire consists of self-control variables using the Self-Control Scale and criminal thinking variables using the TCU Criminal Thinking Scale (TCU CTS), each of them consist 24 statement items. Data analysis used descriptive test, normality test, linearity test, simple linear regression test, significance test, and determination test with IBM SPSS 26.0 software. There are research results that the value of t arithmetic > t table (5,497 > 1,989) where t arithmetic is negative which means it is inversely proportional. So that Ho is rejected and Ha is accepted, which means that there is a significant and negative effect of self-control on the criminal thinking of prisoners at Correctional Institution Class I Surakarta. The results of the determination test obtained R square value of 0.265 which indicates that the magnitude of the influence of self-control on criminal thinking of prisoners is 26.5% while the remaining 73.5% is influenced by other factors